Gingival hyperplasia by upper airway obstruction - Díaz Soriano, Ana (2009)
The effects of mouth breathing are the introduction of cold air, dry and dusty in the mouth and pharynx, the lost functions of heating, humedificacion and filtering the air entering the nose increases the oral mucosa irritation and pharyngeal. A case of a female patient 15 years old who comes for consultation of Periodontology with increase in volume and gingival redness in the upper anterior sector of upper airway obstruction caused by deviated septum right turbinate hypertrophy and maxillary sinusitis. This raises the clinical features, diagnosis, and treatment plan. After treatment of periodontal disease, patients will be transferred to hospital for a recommendation from the specialist septoplasty.